Multi‐Structure Hollow Nanofibers: Controlled Synthesis and Photocatalytic Applications. Issue 8 (10th June 2020) - Liu, Jing; Liu, Xiaofeng; Li, Dianming; Yue, Guichu; Li, Huaike; Li, Shuai; Gao, Songwei; Wang, Nü; Cui, Zhimin; Bai, Jie; Zhao, Yong
Abstract: Solar‐driven semiconductor photocatalysts for solving global energy shortage and environmental pollution have attracted massive attention. Multi‐structure hollow nanofibers (MSHFs) photocatalyst offers many advantages, including abundant surface area for multiple light harvesting and interface redox reaction, heterostructured thin shell for expediting charge separation and transportation and large length‐diameter ratio for easily recycling. Herein, we summarize the latest development of MSHFs materials in terms of controlled synthesis approaches and applications in photocatalysis. The synthetic strategies are mainly classified into two categories, containing templating method and electrospinning approach. These MSHFs have wide applications in H2 production, CO2 reduction, organic compound degradation and dye‐sensitized solar cells (DSSCs). To the end of the review, perspectives on the future research and development of MSHFs are also discussed. Abstract : Got fiber ? Multi‐structure hollow nanofibers are emerging photocatalytic materials, which have unique characteristics. Hollow space and multi‐structure provide abundant surface area for light harvesting and interface reaction. Heterojunction accelerates charge separation and transport. The large length‐to‐diameter ratio makes them easy to recycle. Here, we summarize the progress of multi‐structure hollow nanofibers in synthesis and photocatalytic applications.